Grain yield and lodging-related traits of ultrashort-duration varieties for direct-seeded and double-season rice in Central China - Xin-yu WANG; Le XU; Xiao-xiao LI; Guo-dong YANG; Fei WANG; Shao-bing PENG (Journal of Integrative Agriculture, 2022)
Lodging is the most common constraint on grain yield of direct-seeded rice. There is limited information about lodging resistance and its related plant traits in direct-seeded and double-season rice (DDR) in Central China. This study aims to identify the plant traits that achieve high lodging resistance in ultrashort-duration varieties (about 95 days) of DDR. Field experiments were conducted in 2017 and 2018 in Wuxue County, Hubei Province, China, with four ultrashort-duration varieties grown under two nitrogen (N) rates. Lodging-related traits were measured on the 15th day after heading, and yield and yield attributes were measured at maturity. The grain yield of the four varieties ranged from 4.59 to 7.61 t ha–1 across the two N rates, with a total growth duration of 85 to 97 days. Varietal differences in lodging index were mainly explained by the bending moment, which was closely related to plant height. Breaking resistance did not affect the lodging index significantly. Shortening plant height from 95.4 to 80.5 cm decreased the lodging index by 22.4% but did not reduce grain yield. Our results suggested that reducing plant height was effective in improving the lodging resistance of ultrashort-duration varieties of DDR. Lodging resistance should be enhanced by improving breaking resistance rather than reducing plant height to increase DDR grain yield further.